Perancangan Sistem Informasi Gedung Olahraga Sinar Kasih - Dwi Setyawan; Muhammad Setiyawan (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2023)
Sinar Kasih GOR is a business in the field of leasing buildings for sports, especially badminton, which is still managed with a manual system, starting from the GOR booking system and checking schedules must be done by coming to the GOR, that's why researchers want to create an information system for Sinar Kasih GOR. An information system is a combination of information technology and the activities of the people who use that technology to support operations and management. In a very broad sense, the term information system that is often used refers to interactions between people, algorithmic processes, data, and technology. This information system was created to help and make it easier for us to obtain data in processing field rental data in order to achieve the company's goal of making the officers' work easier with this leasing information system facility.